PENGARUH MEDIA PEMBELAJARAN PAPAN DAN KARTU MISTERI TERHADAP KEMAMPUAN BERBICARA SISWA PADA MATA PELAJARAN BAHASA INDONESIA MI MA’ARIF CEKOK, BABADAN, PONOROGO - Devi Rovi'atus Sholikhah; Farida Yufarlina Rosita (Institut Agama Islam Negeri Ponorogo, 2023)
This study aims to prove whether board learning media and mystery cards can be applied as an effort to improve students' speaking skills, the effect of board and mystery cards learning media on students' speaking ability. Using a quantitative approach to the type of experimental research. Data collection in this study used test instruments in the form of pre-test and post-test. Based on the results of data analysis, it was shown that board and mystery card learning media could improve students' speaking skills. This is evidenced by the increased post-test results in the experimental class, and the influence of board and mystery card learning media onstudents' speaking abilities, evidenced by the results of the independent sample t test, which shows t count 8.792 greater than t table 2.02439, and a significance value of 0.000 < 0.05. This means that Ho is rejected and Hi is accepted, so it can be concluded that there is a significant effect of board and mystery cards learning media on students' speaking abilities in the Indonesian language subject MI Ma'arif Cekok, Babadan, Ponorogo.